The influence of promotion mix, brand image, and level of motivation on repurchase intentions through the decision to stay at Grand Wahid Salatiga Hotel - Wahyu Andung Ramadhan (Publikasi Indonesia, 2024)
The COVID-19 pandemic has seriously impacted the tourism sector, especially the hotel industry in Indonesia. Restrictions on travel and community activities have drastically declined hotel room occupancy rates and overall hotel industry revenues. This research aims to understand to what extent the Grand Wahid Hotel Salatiga can survive and strengthen its existence after the COVID-19 pandemic. With a focus on the influence of the promotional mix on the decision to stay at a hotel, this research involves analysis of promotional aspects, brand image and consumer behavioural motivation. This approach will provide deeper insight into the strategies needed to recover and strengthen the hospitality industry after the pandemic. This research uses an explanatory research method, with quantitative data used. The data collection technique used non-probability sampling techniques, using 100 respondents who had stayed at the Grand Wahid Hotel Salatiga, and then the data was analysed using SEM-PLS. The results show that promotional mix, brand image and consumer motivation significantly influence decisions. Within the framework of Planned Behavior theory, the findings highlight the role of attitudes, subjective norms, and perceived behavioural control in influencing individuals' intentions to stay at a hotel. This research concludes that the promotional mix positively affects the decision to stay at the Grand Wahid Hotel Salatiga, indicating that the more promotional media there are, the more respondents' interest will increase. A good brand image and superior service quality also positively influence the decision to stay.